Operational Management and UX Optimization on Lazada Mobile Top Up Page - Violina Setiawan; Denta Felli Ananda; Aulia Danibrata; Erika Jimena Arilyn (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This MBKM final report contains the author's overall activities during internship in Lazada's Key Account Management Digital Goods division. This report will be preceded by an introduction that covers the government's MBKM program in outline. After that, the report will be continued with the activities carried out by author, both routine and non-routine, complemented by the process to constraints and solutions. Where, author's main activity during internship in this division was to manage operations and also the final project in the form of UX optimization on Lazada mobile top up page. This report will also focus on the knowledge, abilities, and other things that author has gained during internship. Author also provide evaluations that could be useful for the next batch of MBKM programs.